Kinematic characteristics of alignment in acrobatic athletes - McNeal, J.; Sands, W. A. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this study was to determine if an underlying structure defining an `aligned` body could be identified in acrobatic athletes, and to assess extreme examples of this structure for specific kinematic differences. Twenty-five male and female competitive gymnasts and divers were assessed for body segment alignment in a straight-standing position. Passive reflective markers were placed on the skin surface covering a variety of anatomical landmarks along the appendages and torso, including the spine. Athletes were instructed to assume the `straightest body position possible` with their arms overhead and eyes forward. An HD digital camcorder recorded this position for approximately 5s. The video was digitized for various angular positions of the upper and lower extremities and the torso. Hierarchical cluster analyses revealed 4 clusters of athletes based on the kinematic variables. Athletes comprising the two most distant clusters (labelled `best` and `worst` with regard to alignment variables) were selected for further comparison. Discriminant and logistic regression identified pelvic tilt relative to vertical and forward head angle as the variables accounting for the most variance between the two groups. Independent t-tests revealed that athletes from the `best` cluster were characterized by a more vertically aligned trunk, upper extremity-sternum, upper extremity-trunk, lower limb, and pelvic tilt, a more forward head position and smaller cervicothoracic angle. Identification of kinematic characteristics associated with an aligned body can help direct coaching and talent identification efforts for achievement of this position.